Implication of the Type IV Secretion System in the Pathogenicity of Vibrio tapetis, the Etiological Agent of Brown Ring Disease Affecting the Manila Clam Ruditapes philippinarum - Rahmani, Alexandra; Delavat, François; Lambert, Christophe; Le Goic, Nelly; Dabas, Eric; Paillard, Christine; Pichereau, Vianney (Frontiers in Cellular and Infection Microbiology, 2021)
Vibrio tapetis is a Gram-negative bacterium that causes infections of mollusk bivalves and fish. The Brown Ring Disease (BRD) is an infection caused by V. tapetis that primarily affects the Manila clam Ruditapes philippinarum. Recent studies have shown that a type IV secretion system (T4SS) gene cluster is exclusively found in strains of V. tapetis pathogenic to clams. However, whether the T4SS is implicated or not during the infection process remains unknown. The aim of this study was to create and characterize a V. tapetis T4SS null mutant, obtained by a near-complete deletion of the virB4 gene, in order to determine the role of T4SS in the development of BRD. This study demonstrated that the T4SS is neither responsible for the loss of hemocyte adhesion capacities, nor for the decrease of the lysosomal activity during BRD. Nevertheless, we observed a 50% decrease of the BRD prevalence and a decrease of mortality dynamics with the virB4 mutant. This work demonstrates that the T4SS of V. tapetis plays an important role in the development of BRD in the Manila clam.